2003
DOI: 10.17796/jcpd.27.3.m46h21173x62jx07
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of mandibular morphology, with specific reference to the antegonial notch and the curve of Spee

Abstract: The purpose of this investigation was to determine whether particular metrical traits of the mandibular antegonial notches are associated with specific mandibular growth patterns, and also with the mean depth of the curve of Spee. Thirty pre-treatment lateral cephalometric radiographs belonging to a randomly selected group of patients treated in the orthodontic clinic at the SUNY at Buffalo were digitized. The surface areas of the mandibular antegonial notches, as well as some sagittal facial dimensions were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
17

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
2
11
0
17
Order By: Relevance
“…9 Depth of the curve of Spee and the length of the mandibular body are decreased when there is an increase in the surface areas of the ANs. 10 In our study also the deep AN was accompanied by the less forward growth of the mandible, hence a short body length. The clinical presence of a deep mandibular AN is indicative of a diminished mandibular growth potential and a vertically directed mandibular growth pattern.…”
Section: Discussionsupporting
confidence: 66%
“…9 Depth of the curve of Spee and the length of the mandibular body are decreased when there is an increase in the surface areas of the ANs. 10 In our study also the deep AN was accompanied by the less forward growth of the mandible, hence a short body length. The clinical presence of a deep mandibular AN is indicative of a diminished mandibular growth potential and a vertically directed mandibular growth pattern.…”
Section: Discussionsupporting
confidence: 66%
“…Tomer and Kishani [20] also found no statistically significant correlation between the craniofacial morphology and depth of the notch. Studies by Salem et al [17] on the surface area of the antegonial notch demonstrated that larger surface area was associated with a trend for greater vertical direction of mandibular growth. They also found that the depth of the curve of Spee describing occlusion, and the length of the mandibular body decreases with increasing surface area of the antegonial notch.…”
Section: Discussionmentioning
confidence: 98%
“…MacIntosh [13] defined it as the "pregonial notch", and Henderson and Poswillo [8] described it as the "antegonial notch". The presence of the antegonial notch was reported by various researchers [2,10,17,19,20]. Information on the presence, location and depth of this notch is important for maxillofacial surgeons during orthognathic treatment of mandibular deformities [16,22].…”
Section: Introductionmentioning
confidence: 96%
“…[4] In humans, an increased curve of Spee is often seen in brachycephalic facial patterns[1213] and associated with short mandibular bodies. [14]…”
Section: Developmentmentioning
confidence: 99%
“…This concept, especially as applied to deep overbite patients, has been supported by others[37–42] and produces variable results with regard to maintaining a level after treatment. [144344]…”
Section: Curve Of Spee – From Flat To Mildmentioning
confidence: 99%